Characterization of Humic Substances from Taiga and Tundra Soils by EPR Spectroscopy - Evgeny Lodygin; Roman Vasilevich; Evgeny Abakumov (Agronomy, 2022)
Paramagnetic activity is a fundamental property of humic substances (HSs). The agricultural use of soils does not only affect the qualitative and quantitative compositions of HSs, but also the content of free radicals (FRs) in their structure. Changes in the composition of incoming plant residues and hydrothermal conditions have an effect on soil humification rates and the paramagnetic properties of humic (HAs) and fulvic acids (FAs). Data on the influence of various factors on the content of FRs in HAs and FAs are not enough. Therefore, the purpose of this study was to examine the influence of the degree of hydromorphism and agricultural use on the paramagnetic properties of HA and FA samples obtained from taiga and tundra soils. Studies have shown that the increased hydromorphism in taiga soils leads to the growing concentration of FRs in the HA molecular structure. HAs in virgin tundra soils exhibit a lower content of unpaired electrons when shifting from automorphic soils to hydromorphic ones. Going from the south to the north, the paramagnetic activity of both HAs and FAs tends to decrease due to the overall reduction of the number of polyconjugated systems in the tundra soil HSs. The comparative analysis of the paramagnetic properties in HAs and FAs of virgin and arable soils revealed that their agricultural use reduces the FR concentration in the structure of HSs, in other words it leads to the accumulation of biothermodynamically stable and more humified compounds in the arable horizons. This contributes to the stabilization of SOM in arable soils.